PENYULUHAN KESEHATAN KEPADA IBU HAMIL DAN NIFAS DI PUSKESMAS MARTUBUNG MEDAN - Tarigan, Yenni Gustiani; Bintang, Mayrosa; Purba, Ivan Elisabeth (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2025)
Maternal and child health services are an integral part of health services, which are directed at realizing family health in order to achieve quality families. The purpose of this community service activity is to assess midwifery services for pregnant and postpartum women at the Martubung Community Health Center, Medan City. This activity was carried out at the Martubung Community Health Center, Medan City on Friday, May 23, 2025 from 08.00 to 11.30 WIB. The instruments used in this community service were interactive lectures, leaflet distribution and simulations. The significant increase in knowledge shows that health education plays an important role in promoting maternal and infant health, and is part of efforts to reduce maternal and infant mortality.